ADMM/ ADMM Plus As Cbm Through Non-Traditional Issues (ASEAN) - Alma Evelinda Silalahi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The ADMM/ADMM Plus is the highest defense consultative and cooperative mechanism in ASEAN. Its primary aim is to promote mutual trust and confidence among participating countries by facilitating a greater understanding of defense and security challenges, as well as enhancing transparency and openness. These initiatives have fostered a conducive atmosphere for military, economic, and socio-cultural cooperation among ASEAN countries. In recent years, non-traditional security issues such as natural disasters, transnational crimes, and pandemics have posed significant challenges to the welfare of ASEAN peoples. This paper examines the ADMM/ADMM Plus as a Confidence-Building Measures through Non-Traditional Issues (ASEAN) using a qualitative approach. The qualitative research methodology allowed for a deep exploration of perceptions of participants in the ADMM/ADMM Plus initiatives, providing valuable insights into the effectiveness of these initiatives in promoting cooperation and addressing non-traditional security challenges. As a result of this research, despite the challenges involved, the ADMM/ADMM Plus has proven to be a highly effective platform for practical cooperation among participating countries' defense establishments. It provides a common ground to further enhance collaboration and associations, and offers a way forward to improving defense relations by implying CBMs. Through the ADMM/ADMM Plus initiatives, a conducive atmosphere for military, economic, and socio-cultural cooperation among ASEAN countries has been promoted, particularly in addressing non-traditional security issues. In conclusion, the ADMM/ADMM Plus has demonstrated its effectiveness in promoting cooperation among ASEAN countries' defense establishments, and in addressing non-traditional security challenges, as revealed through the insights gathered from this qualitative study